2017
DOI: 10.12659/msm.899580
|View full text |Cite
|
Sign up to set email alerts
|

Revision Knee Arthroplasty in Patients with Inherited Bleeding Disorders: A Single-Center Experience

Abstract: BackgroundThe results of total knee arthroplasty (TKA) in patients with inherited bleeding disorders (IBDs) are poorer when compared with those in the general population, with a notably higher risk of complications and higher revision rates. Thus, revision procedures are becoming a growing concern in this group of patients. The aim of this study was to evaluate the results of revision TKA in patients with IBD.Material/MethodsA retrospective cohort study with longitudinal assessment of hemophilia patients sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
22

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 43 publications
1
6
0
22
Order By: Relevance
“…Previous studies have included either a mixed cohort of patients with haemophilia and VWD or include other major orthopaedic surgeries such as total ankle arthroplasty or spinal surgery . The largest cohorts consist of patients with coagulopathy who have been identified from a commercial database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have included either a mixed cohort of patients with haemophilia and VWD or include other major orthopaedic surgeries such as total ankle arthroplasty or spinal surgery . The largest cohorts consist of patients with coagulopathy who have been identified from a commercial database.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary literature about the perioperative complications of hip and knee arthroplasty patients with bleeding disorders often include mixed cohorts of haemophilia and von Willebrand disease, making the results of these studies difficult to interpret. There is a paucity of data on the frequency and incidence of complications with isolated VWD .…”
Section: Introductionmentioning
confidence: 99%
“…Ten-year survival rates for knee arthroplasty implants have been reported to be as high as 94.3% [11]. However, investigations have found that TKA in these patients is associated with high rates of infection, intraoperative complications, and revision surgeries [6,[12][13][14][15][16][17][18]. The prevalence of infection after primary TKA in patients with hemophilia ranges from 0 to 17% in the literature, which is higher than the reported prevalence of 1-2% seen in TKA patients who do not have hemophilia [12].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the outcomes and complications in the experience of our centre, they are comparable with those reported in the literature. [14][15][16] The higher frequency of our early bleeding events (23%) in the first period of observation, above all during emergency interventions, has been controlled, due to more generous replacement with factor concentrates in the second period (3.2%). 9 Infections, encountered in 13% of the cases, will have to remain under our strict attention.…”
Section: Discussionmentioning
confidence: 99%